Understanding Racism in Europe: Historical Roots, Contemporary Challenges, and Paths to Equality - Andrea Baltasar (International Journal of Science and Society, 2023)
Racism has long been a pervasive issue in Europe, with deep historical roots that continue to manifest in contemporary society. This scholarly article explores the historical context of racism in Europe, examines the current challenges faced by marginalized communities, and discusses potential avenues for combating racism and promoting equality in the region. Through an interdisciplinary approach, this article aims to shed light on the complex and multifaceted nature of racism in Europe.